Religious Pluralism - Buhr, João Rainer (Vox Scripturae - Revista Teológica Internacional, 2025)
A very current topic in theology is religious pluralism. The purpose of the article is to reflect on the factors that contributed to the emergence of this thought. A better understanding of its source is reached through the analysis of postmodernism. The basic principles that support it are also analyzed. Finally, the fundamental ideas of religious pluralism are confronted with the bible.